2021
DOI: 10.3390/app11104556
|View full text |Cite
|
Sign up to set email alerts
|

The UWB Radar Application in the Aviation Security Systems

Abstract: In the process of our research, we have identified new methods of processing ultra-wide-band (UWB) radar signals and possibilities of the UWB radar use in aviation security systems. We paid our main attention to finding new algorithms for tracking the movement of a person behind an obstacle using the UWB radar. Such UWB radar application is typical for tracking the movement of people behind obstacles in case of security forces intervention at an airport. In the research process, we used methods of analysis, sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Hardware components of UWB radars were presented in [ 23 ]. In [ 24 ], the authors identified new methods of processing UWB radar signals and possibilities of the UWB radar use in aviation security systems. The authors of [ 25 ] present a conceptual guide to the UWB impulse signal and target interaction phenomenon showing how to use the signal spectrum change to identify and enhance detection and tracking of certain target classes.…”
Section: Uwb Radar Applicationsmentioning
confidence: 99%
“…Hardware components of UWB radars were presented in [ 23 ]. In [ 24 ], the authors identified new methods of processing UWB radar signals and possibilities of the UWB radar use in aviation security systems. The authors of [ 25 ] present a conceptual guide to the UWB impulse signal and target interaction phenomenon showing how to use the signal spectrum change to identify and enhance detection and tracking of certain target classes.…”
Section: Uwb Radar Applicationsmentioning
confidence: 99%
“…Although SMEs are aware of the existence of business risk, they perceive it with different intensity (Bartos et al, 2021). Many companies use mainly informal risk assessment (Antosko et al, 2015;Petruf et al, 2015), although in technological processes, increasingly more sophisticated system and predictive mechanisms are implemented (Főző et al, 2019;Kužma et al, 2016;Džunda et al, 2021). Moreover, some companies do not have the appropriate organisational condi-tions for the functioning of a department responsible for the analysis and risk management (Machova & Vochozka, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Literature [1] studied the related technologies of Ultra-wideband radar imaging, and gave the key problems and solutions of Ultra-wideband radar imaging. Literature [2] studied and discussed the application of Ultra-wideband radar in aviation safety system. Literature [3] proposed an improved target recognition algorithm based on carrier-free Ultrawideband radar to improve the target recognition effect of Ultra-wideband radar.…”
Section: Introductionmentioning
confidence: 99%